Safety evaluation of major hazard installations based on regional disaster system theory. (March 2021) - Yang, Ping; Huang, Xianjia; Peng, Lan; Zheng, Zeming; Wu, Xiaodong; Xing, Chaoliang
Abstract: Major accidents have catastrophic effects on humans and all of society. To prevent the occurrence of major accidents, it is essential to strengthen the management of major hazard installations. Generally, effective identification and reasonable evaluation of major hazard installations are the basic steps in safety management. At present, the evaluation methods for major hazard installations mainly focus on consequence analysis and probabilistic analysis without considering the vulnerability of hazard-affected bodies. Therefore, the proposed method will introduce regional disaster system theory and comprehensively analyze hazard-formative factors, the hazard-formative environment and hazard-affected bodies to achieve a more complete and effective assessment of major hazard installations. Hazard-formative factors are evaluated based on the rapid ranking method, hazard-formative environments are evaluated based on Bayesian networks, and hazard-affected bodies are evaluated based on the fuzzy comprehensive evaluation method. A tank group and a chemical industrial park are used to verify the feasibility and effectiveness of the new method. Highlights: A new safety evaluation framework is established for major hazard installations. The framework includes hazard-affected bodies, hazard-formative factors and hazard-formative environment. Two examples are used to verify the feasibility and effectiveness of this method.